The Mechanism of Color Change in the Neon Tetra Fish: a Light‐Induced Tunable Photonic Crystal Array1. Issue 42 (27th April 2015) - Gur, Dvir; Palmer, Benjamin A.; Leshem, Ben; Oron, Dan; Fratzl, Peter; Weiner, Steve; Addadi, Lia
Abstract The fresh water fish neon tetra has the ability to change the structural color of its lateral stripe in response to a change in the light conditions, from blue‐green in the light‐adapted state to indigo in the dark‐adapted state. The colors are produced by constructive interference of light reflected from stacks of intracellular guanine crystals, forming tunable photonic crystal arrays. We have used micro X‐ray diffraction to track in time distinct diffraction spots corresponding to individual crystal arrays within a single cell during the color change. We demonstrate that reversible variations in crystal tilt within individual arrays are responsible for the light‐induced color variations. These results settle a long‐standing debate between the two proposed models, the "Venetian blinds" model and the "accordion" model. The insight gained from this biogenic light‐induced photonic tunable system may provide inspiration for the design of artificial optical tunable systems.